Serum TNF-α and IL-10 levels during chronic carrageenan inflammation with thrombin inhibitor administration in rats - Shevchenko, V. O.; Pavlova, O. O. (Regulatory Mechanisms in Biosystems, 2024)
Inflammatory cytokines are key mediators involved in the activation of the blood coagulation system, influencing various coagulation mechanisms, while activated coagulation proteases, physiological anticoagulants, and fibrinolytic system components can, conversely, modulate inflammation through specific cellular receptors. This study investigated the impact of the thrombin inhibitor dabigatran etexilate on a rat model of secondary chronic aseptic inflammation induced by an intramuscular injection of 10 mg of λ-carrageenan in 1 mL of isotonic saline into the right thigh of rats. Dabigatran etexilate was administered intragastrically via gavage at a dose of 15 mg/kg/day in 1 mL of isotonic saline daily for 28 days. Peripheral blood samples were collected on days 0, 1, 7, 14, 21, and 28 to determine serum TNF-α and IL-10 levels. During the natural course of secondary chronic carrageenan-induced inflammation, serum TNF-α levels increased until day 14 and subsequently decreased gradually towards day 28. Serum IL-10 levels during the natural course rose until day 21, followed by a slight drop on day 28. The administration of dabigatran etexilate modulated these cytokine dynamics, leading to a reduction in TNF-α levels compared to the natural course, particularly on days 14 and 21. Notably, IL-10 levels were significantly higher from day 1 to day 21 during dabigatran etexilate administration and exhibited a biphasic response, with a significant peak on day 7 and the highest levels observed on day 21. These distinct TNF-α and IL-10 level dynamics suggest a strong interaction between proinflammatory and anti-inflammatory processes. Dabigatran etexilate influenced the cytokine profile during chronic inflammation, potentially mitigating the inflammatory response as evidenced by the altered TNF-α and IL-10 levels. These findings highlight the potential of thrombin inhibitors, specifically dabigatran etexilate, in modulating inflammatory responses, warranting further investigation into its therapeutic mechanisms. Future research should focus on exploring the specific mechanisms through which dabigatran etexilate, and potentially other thrombin inhibitors, exert their anti-inflammatory effects, including their influence on humoral mediators relevant to the pathogenesis of chronic inflammation.